Youth, Unemployment and the Social Life of Waiting in Postwar and Postsocialist Bosnia-Herzegovina - Hromadzic, Azra (Ревија за социјална политика/Journal of Social Policy, 2014)
The socio-political and economic environment in which young Bosnians come of age emerged as a result of larger global restructuring from socialism to neoliberalism, and from war to postwar external state-making. This fragile and uncertain context of „double transition“ (Gligorov 2000) encourages political and economic uncertainty, which leaves many youth citizens disoriented and unprepared to engage in a fight for social welfare. Left without a socialist government to take care of their basic needs, prospects and employment, many young people, exhausted by the legacies of war traumas, and worn-out from the undergoing struggles for “bare life” (Agamben 1998) – rudimentary physical and economic survival – find themselves perpetually unemployed. As a result, they withdraw from any political public while „passively“ waiting for better times to arrive and/or hoping to permanently leave their „elsewhere state“ (Jašarević n.d.).
Keywords: youth; unemployment; Bosnia and Herzegovina